English Camp Assistance Using Need Analysis to Strengthen Students' Speaking Skill at SMA Muhammadiyah 1 Gresik - Noviatul Rochmah; Candra Hadi Asmara (Jetlal, 2022)
Community service activities are carried out at SMA Muhammadiyah 1 Gresik which is located on JL. Dr. Wahidin Sudirohusodo No. 162, Setigi, Randuagung, Gresik. The form of this activity is an outdoor activity of an English Camp which was held for two days from October 17-18, 2021. This activity aims to improve students' speaking skills. The implementation of this English Camp assistance was carried out using need analysis activity by conducting interviews with English teachers at the school. The results show that students want a form of English learning that is different from what they receive in class and can implement in daily activities, especially during school hours. Furthermore, it is hoped that the output of the activity will make students more motivated to improve their speaking skills. In addition, teachers can also facilitate with various interactive learning media so that they can create fun learning activities.